Kidney Agenesis and Müllerian Duct Anomalies: A Report of Two Cases and Literature Review - Donielaitė-Anisė, Kamilė; Marozas, Rytis; Bumbulienė, Žana; Jankauskienė, Augustina (Acta medica Lituanica, 2025)
Background: The association between urinary tract anomalies and Müllerian duct anomalies (MDA) is well-known, due to their shared embryonic origin. Disruptions in early development can significantly affect both the kidney and reproductive systems. This article presents two cases illustrating the coexistence of kidney agenesis and MDA in girls, followed by a literature review.Materials and Methods: A literature search was conducted on PubMed, focusing on publications from 2000 to 2024 by using keywords: ‘kidney agenesis’, ‘renal agenesis’, ‘Müllerian duct anomalies’, ‘OHVIRA’ (obstructed hemivagina and ipsilateral renal anomaly), and ‘Herlyn-Werner-Wunderlich syndrome’. The PRISMA guidelines were followed for the study selection. Additionally, two cases managed at Vilnius University Hospital Santaros Klinikos between 2022 and 2024 are presented.Results: The literature search yielded 32 articles encompassing data on 43 girls with an average age of 11.8 years. In 54% of the cases, the diagnosis of kidney agenesis was concurrent with identifying MDA. In other cases, kidney anomalies were detected earlier, including 6 cases identified prenatally. Type III MDA, as classified by the American Fertility Society, was the most common variety. Premenarche diagnosis of MDA was made in 11.9% of the cases. In more than half of the cases, MDA was identified due to complaints necessitating consultations, mostly leading to urgent surgical interventions. At our hospital, a 9-year-old and a 14-year-old were diagnosed with Herlyn-Werner-Wunderlich syndrome. Kidney agenesis was diagnosed prior to MDA in both cases. For the 9-year-old girl, MDA was found incidentally on ultrasound, while the other required consultation and an urgent surgery due to symptoms.Conclusions: Unilateral kidney agenesis frequently co-occurs with Müllerian duct anomalies, highlighting the need for comprehensive evaluations in affected patients. An early diagnosis and management of MDA are crucial to prevent complications. An increased clinical awareness and further research are necessary to enhance early detection and patient outcomes.
Keywords: kidney agenesis; renal agenesis; Müllerian duct anomalies; OHVIRA; Herlyn-Werner-Wunderlich syndrome